2013
DOI: 10.1088/2041-8205/769/1/l18
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Non-Radial Penumbra in a Flux Emerging Region Under Chromospheric Canopy Fields

Abstract: Technical skills of Dr. Yurchyshyn include many-year experience in solar observations with various groundbased solar instruments, substantial experience with acquisition, processing and scientific analysis of space-based observations, and deep physical understanding and broad knowledge of solar phenomena. He actively participated in design and construction of BBSO's full disk Halpha telescope and developed the telescope control and data acquisition software. Managerial performance Dr. Yurchyshyn has organized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 15 publications
6
23
0
Order By: Relevance
“…This is also supported by the studies of Lim et al (2013) and Zuccarello et al (2014), who found no changes in the structure of chromospheric magnetic fields during the formation of orphan penumbrae.…”
Section: Discussionsupporting
confidence: 75%
“…This is also supported by the studies of Lim et al (2013) and Zuccarello et al (2014), who found no changes in the structure of chromospheric magnetic fields during the formation of orphan penumbrae.…”
Section: Discussionsupporting
confidence: 75%
“…The data also clearly showed that the flare related increase of the magnetic field intensity occurred due to both reconfiguring of coronal magnetic fields (i.e., formation of a PEA rooted in the umbra) and emergence of a new flux. We note that there were other locations where photospheric field changed, such as the appearance of a "orphan" penumbra (Strous & Zwaan 1999;Cheung et al 2008;Yurchyshyn et al 2012;Kuckein et al 2012;Lim et al 2013) developed under a stable chromospheric filament, although it is not obvious that these changes either led to or were caused by the flare.…”
Section: Discussionmentioning
confidence: 84%
“…An irregular granulation pattern first appeared there at the flare onset and then developed into an extended system of elongated granules and short penumbra-like filaments (called "orphan" penumbra, arrow in panel f). This pattern is known to be associated with low lying horizontal fields and may indicate the presence of either Ω or U-shaped fields (Strous & Zwaan 1999;Cheung et al 2008;Yurchyshyn et al 2012;Kuckein et al 2012;Lim et al 2013). However, this penumbra like pattern was only associated with positive polarity fields, which according to Figures 7 and 8 appeared to be under a chromospheric filament, FL, that remained undisturbed throughout the flare.…”
Section: Evolution Of the Photospheric Fieldsmentioning
confidence: 98%
“…1 Observations of orphan penumbrae (Zirin & Wang 1991;Kuckein et al 2012;Lim et al 2013;Jurčák et al 2014b;Zuccarello et al 2014) show that they are comparable in all aspects to regular sunspot penumbrae. These observations prove that sufficient magnetic flux is not a necessary condition for a penumbra formation.…”
Section: Introductionmentioning
confidence: 96%